International Capital Mobility and Financial Fragility - Part 2. The Demand for Safe Assets in Emerging Economies and Global Imbalances New Empirical Evidence - Ahrend, Rudiger (OECD Publishing, 2012)
Mismatches between the supply and the demand of safe financial assets in fast-growing emerging countries have been singled out by economic theory as drivers of international capital flows and, ultimately, global current account imbalances. This paper assesses empirically the contribution of the search for safe assets to the size and composition of emerging countries' international asset portfolios. Excess demand for safe assets in financially less-developed countries would imply that these countries hold disproportionately high shares of their total portfolios in foreign assets. Moreover, financially lessdeveloped countries would be expected to hold disproportionately high shares of their foreign portfolios in financially highly-developed countries, as ostensibly safe assets are predominantly produced by the latter. This paper finds little empirical support for these predictions. Financially less-developed countries allocate a larger proportion of their total holdings to domestic assets. Even when focusing on less-developed countries' foreign portfolios, there is no evidence of a general bias toward the assets of financially highlydeveloped countries. Overall, asset mismatches do not appear to be significant drivers of asset allocation of financially less-developed countries
Keywords: Economics